PLD.52 Management and outcome of patients with Pre-labour Spontaneous rupture of membranes. (9th June 2014) - Annamraju, H; Karnad, R; Benson, C; Miller, V
Abstract : Study: Retrospective, during September–October 2010. Patients: 90 patients, in a District General Hospital. Aim: To look at the management and outcome of Pre-labour Spontaneous Rupture Of Membranes (SROM). Results: We looked at the method of confirmation of SROM including history (24%), speculum examination (43%), ultrasound scan (7%) and pad checks (23%). There was no information in 2 patients. 50 patients went into spontaneous labour and 42% were induced. The method used for induction was syntocinon for most of the women (92%). Only 3 women received prostin. 13 patients in all (14%) needed artificial rupture of membranes (ARM) in labour. Of the total 90 women, 17 women had caesarean sections (19%). But of the women who were induced, 10 women (26%) had c-sections: 6 for fetal distress and 4 for failure to progress. 10 babies went to SCBU. Of them 2 did not receive intrapartum antibiotics. In general 92% received IV antibiotics in labour. Conclusion: Given that 26% of the inductions ended up with caesarean section, it may be worth considering the use of prostin/ propess for the primips, and ensuring the appropriate use of syntocinon. As 13 patients needed ARM in labour, accuracy in the diagnosis of SROM plays an important role.